1983
DOI: 10.1079/bjn19830022
|View full text |Cite
|
Sign up to set email alerts
|

BJN volume 32 issue 1 Cover and Back matter

Abstract: 1. Total heat loss was measured by 24 h direct calorimetry in five obese and five lean women who were maintained throughout the study on a diet supplying 3·3 MJ/d. Each subject was measured five times to assess the effect of temperature, exercise and food on energy expenditure. Within each weight group a Latin-square design was used to balance sequence effects on the thermogenic responses to temperature, exercise and food.2. Compared with the control day, on which no thermogenic stimulus was given, the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This highlights the seasonal effects on metabolism and various ways that individuals respond to cold stress (insulative:vasoconstriction vs. metabolic:thermogenesis), which the authors point out could have potential implications for subject specific energy balance [79]. A divergent response between lean and obese women to T a is observed with heat loss being decreased at cool T a in obese subjects (−2.1%) and increased in lean subjects (+7.8%; but not statistically significant) [81]. When comparing lean and obese men subjected to cooling, both groups had an increase in metabolism, but the relative increase was significantly larger in lean subjects [34].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the seasonal effects on metabolism and various ways that individuals respond to cold stress (insulative:vasoconstriction vs. metabolic:thermogenesis), which the authors point out could have potential implications for subject specific energy balance [79]. A divergent response between lean and obese women to T a is observed with heat loss being decreased at cool T a in obese subjects (−2.1%) and increased in lean subjects (+7.8%; but not statistically significant) [81]. When comparing lean and obese men subjected to cooling, both groups had an increase in metabolism, but the relative increase was significantly larger in lean subjects [34].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies in human subjects consistently found inverse associations between ambient temperature and energy expenditure under standardized conditions (i.e. for clothes, food intake and/or physical activity) [ 11 - 17 ]. An Italian observational population-based cohort study of 1597 Caucasian adults investigated the association between indoor temperature reported at baseline and incident obesity during 6 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%